Utilization of induction-machine mathematical model for measuring technique - Schejbal, Vladimír; Novák, Jaroslav; Gregora, Stanislav (Univerzita Pardubice, 2004)
The design, application and capability of a measuring equipment, used for testing electromechanical systems, especially drive units with induction motors, are presented. The equipment function is based on the computation of an induction machine current model with increased accuracy. The main attention is paid to indirect torque determination by real-time Computation.
Keywords: indukční stroje; měřící technika; elektromechanické procesy; matematické modely